Evaluation of body composition and aerobic capacity of elderly walkers (Research, Society and Development, 2020)
Objective: To evaluate the body composition and aerobic capacity of elderly walkers Methodology: The approach used in this article is field research, which is quantitative and descriptive. Using as a research tool the systematic collection of data on a group of 12 elderly people. The following tests were performed: mile test of 1600 meters to assess aerobic capacity and strength test of the lower limbs to sit and stand up from the chair. In addition, the Body Mass Index and Fat Percentage were collected. Results: The results showed a statistically significant difference in relation to Body Mass, Fat Percentage and VO2Máx between genders. In addition, a significant correlation was found between the sit and stand test with VO2Máx. Conclusion: It was evidenced that, in our sample, a greater capacity of VO2Máx in the male population, when compared to the female. Finally, the importance of maintaining daily physical activity is emphasized, especially the elderly population for maintaining their functional capacity and quality of life.